STUDIES ON DEVELOPMENT OF READY-TO-SERVE (RTS) BEVERAGES FROM WOOD APPLE (LIMONIA ACIDISSIMA L.), GUAVA (PSIDIUM GUAJAVA L.), GINGER (ZINGIBER OFFICINALE ROSCOE) AND CARDAMOM (ELETTARIA CARDAMOMUM MATON) BLEND - MOHAMMAD ISHAN,; BHAGWAN DEEN, (The Bioscan, 2025)
The present investigation was carried out at Post Graduate Laboratory, Department of Post-Harvest Technology, College of Horticulture & Forestry, Acharya Narendra Deva University of Agriculture and Technology, Kumarganj, Ayodhya-224229, U.P. India during 2025. Wood apple (Limonia acidissima L.), Guava (Psidium guajava L.), Ginger (Zingiber officinale Roscoe) & Cardamom (Elettaria cardamomum Maton) have nutritional, spicy, medicinal and therapeutic values. In the present studies, wood apple pulp, guava pulp, ginger juice and cardamom seed extract were blended in different ratios viz., 0:90:9:1 (T1), 10:80:9:1 (T2), 20:70:9:1 (T3), 30:60:9:1 (T4), 40:50:9:1 (T5), 50:40:9:1 (T6), 60:30:9:1 (T7), 70:20:9:1 (T8), 80:10:9:1 (T9), 90:0:9:1 (T10) for the preparation of RTS. Result appears that the treatment no. 4 containing 30% wood apple pulp + 60% guava pulp + 9% ginger juice + 1% cardamom seed extract was found to be best over other treatments for the preparation of palatable quality of RTS blend beverages. Therefore 10% blend with 13% Total Soluble Solids, 0.3% acidity and incorporated with 70 ppm SO2 was used to prepare RTS for storage study. During the storage period TSS, acidity, reducing sugars, total sugars and browning increased whereas, ascorbic acid (Vitamin-C), non-reducing sugar, and organoleptic quality decreased with the advancement of storage period. The beverage was organoleptically acceptable upto 3 months of storage in ambient condition.